Technical-economic performance of fuel cell integration in autonomous hybrid systems - Bayoud, Mebarka; Ghoudelbourk, Sihem; Mohamed Nassim Bouzidi, Belgacem (Institute of Advanced Engineering and Science, 2025)
Increasing energy demand and greenhouse gas emissions reinforce the importance of renewable resources in energy systems. This study evaluates the technical and economic viability of integrating a fuel cell (FC) in autonomous hybrid systems to supply a community in Algeria, with an average power of 6.91 kW and a daily energy requirement of 165.6 kWh. Four hybrid system configurations were compared using HOMER software: i) photovoltaic (PV) and batteries (BAT), ii) PV, BAT, and diesel generator (DG), iii) PV, BAT, and FC, and iv) PV, BAT, DG, and FC. The PV/BAT/DG/FC system was identified as the optimal configuration, balancing energy efficiency, reducing energy surpluses, reducing reliance on DG, and reducing CO2 emissions while maintaining competitive energy costs. These results demonstrate that the integration of FC can improve the sustainability and stability of autonomous hybrid energy systems.